Self-Care Pattern among Mature Woman with Hypertension at Karyawangi Village of Parongpong District of Bandung Regency: A Phenomenological Study - Simanjuntak, Samuel M. (11th International Scholars Conference, 2018)
Hypertension, known as the silent killer, is a condition where the systolic blood pressure is more than 120 mmHg and diastolic pressure is more than 80 mmHg. The study explored the patient’s self-care patterns toward the hypertension, environmental patterns, family roles, coping method, and how to obtain health assistance. This study made use of qualitative-phenomenological methods of research by conducting an in-depth interview on seven respondents utilizing ten semi-structured questions. The participants were selected using the purposive sampling with inclusion and exclusion criteria. The following themes were identified after the conduct of the study: self-physical, emotional condition, cognator, mastery experience, vicarious experience, self-concept, self-efficacy, persuasion, regulator and interdependence. The study also recommended that other characteristics from each category be explored such as patient self-care patterns and lifestyle patterns. It also recommended that the health officer provide clear information that is easy to understand. Furthermore, regular health education must be provided among mature woman.